Elements of the Near and Middle East in the Culture of the Transylvanian Romanians from Brașov (1848-1918) - MIC, Andrei (Studia Universitatis Babeș-Bolyai Historia, 2025)
In the present paper, we first aim to provide a brief historical context of the issue (second half of the fourteenth century – beginning of the nineteenth century) aiming to highlight the means by which the inhabitants of the Transylvanian town of Brașov / Kronstadt came into contact with the multiple facets of the Near and Middle East. We also intend to chronologically and thematically reconstruct the various oriental elements found in the culture of the local Transylvanian Romanians between the 1848 Revolution and the end of World War I. The aim of this approach, which is a novelty for the Romanian historical writing, is to examine whether and how the inhabitants from Brașov maintained their contacts with this exotic space throughout modernity. Our analysis is based on a series of articles, correspondence, literary creations (anecdotes, fairy tales, poems, short stories, proverbs, prose, translations), different editions of documents, school textbooks in geography, history and Romanian language, memoirs, press magazines of the time (Foaie pentru Minte, Inimă și Literatură, Gazeta Transilvaniei), culinary recipes, as well as on Romanian and foreign historiography relevant to the subject. Rezumat: În lucrarea de față, ne propunem mai întâi să formulăm un scurt context istoric al problemei (a doua jumătate a secolului al XIV-lea – începutul secolului al XIX-lea) pentru a vedea cum au început cetățenii Brașovului să intre în contact cu multiplele fațete ale Orientului Apropiat și Mijlociu. De asemenea, ne dorim să reconstituim cronologic și tematic variatele elemente orientale regăsite în cultura românilor ardeleni din Brașov între Revoluția Pașoptistă (1848-1849) și sfârșitul Primului Război Mondial (1914-1918). Scopul acestui demers, care este o noutate pentru scrisul istoric românesc, este de a examina dacă și cum au perpetuat brașovenii contactele lor cu acest spațiu exotic pe parcursul modernității. Întreaga noastră analiză se va baza pe o serie de articole, corespondențe, creații literare (anecdote, basme, poezii, povestiri, proverbe, proze, traduceri), ediții de documente, manuale școlare de geografie, istorie și limba română, memorii, presa epocii (Foaie pentru Minte, Inimă și Literatură, Gazeta Transilvaniei), rețete culinare, dar și pe istoriografia română și străină relevantă subiectului. Cuvinte-cheie: Orientul Apropiat, Orientul Mijlociu, Transilvania, Brașov, identitate, alteritate, modernitate